2017
DOI: 10.1371/journal.pone.0178100
|View full text |Cite
|
Sign up to set email alerts
|

Maternal low thyroxin levels are associated with adverse pregnancy outcomes in a Chinese population

Abstract: Although thyroid dysfunction in early pregnancy may have adverse effects on pregnancy outcomes, few studies have examined the relationship between maternal low free thyroxin (FT4) levels in both first and third trimesters of pregnancy and the incidence of adverse pregnancy outcomes. We hypothesized that low FT4 levels in either first or third trimesters of pregnancy may have different effects on pregnancy outcomes. The study included 6,031 mothers who provided both first and third pregnancy serum samples for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 41 publications
2
25
1
Order By: Relevance
“…Previous work has suggested that fT4 concentrations early in pregnancy are inversely associated with odds of GDM [61,68]. In accordance with those ndings, the ratio of fT3 to fT4 has been observed to be positively associated with odds of GDM [69], suggesting that increased conversion of T4 to biologically active T3 may play a role in the onset of GDM.…”
Section: Gestational Diabetes Mellitussupporting
confidence: 78%
See 1 more Smart Citation
“…Previous work has suggested that fT4 concentrations early in pregnancy are inversely associated with odds of GDM [61,68]. In accordance with those ndings, the ratio of fT3 to fT4 has been observed to be positively associated with odds of GDM [69], suggesting that increased conversion of T4 to biologically active T3 may play a role in the onset of GDM.…”
Section: Gestational Diabetes Mellitussupporting
confidence: 78%
“…Previous studies have found increased odds of preeclampsia with higher second trimester fT4 concentrations [20,60], and lower third trimester fT4 concentrations [61]. All associations we observed between fT4 and preeclampsia were inverse, although not statistically signi cant.…”
Section: Preeclampsiacontrasting
confidence: 50%
“…A prospective study of 6,031 Chinese pregnant women showed that low FT4 levels during pregnancy were a risk factor for GDM and preeclampsia (395). On the contrary, the incidence of GDM decreased in women with higher FT4 levels, showing a protective effect for the development of GDM (396).…”
Section: Advance Article: Endocrine Reviewsmentioning
confidence: 99%
“…Both studies are thus vulnerable to a high risk of false positive findings; therefore, further studies are needed. Other studies showed association between maternal isolated hypothyroxinemia with breech presentation or Cesarean section (28), preeclampsia (29) and macrosomia (11,28), the results from these isolated observational studies require additional confirmation. Thus, current evidence continues to support the statements made in the 2017 ATA Guidelines regarding isolated hypothyroxinemia in pregnancy.…”
Section: C) Treatment Of Subclinical Hypothyroidism (Question 37)mentioning
confidence: 85%
“…/228) of women with hypothyroxinemia in both the first and third trimesters, aOR 2.62, CI 1.23-5.62 and 2.87% (15/523) of women with hypothyroxinemia in only the third trimester, aOR 2.16, CI 1.22-3.82. Women in the second trimester of pregnancy were not included in this study(29). In the prospective study by Yang et al the authors reported an association between isolated hypothyroxinemia and rates of macrosomia compared to euthyroid controls, 19.6% (9/46) vs. 10.8% (95/882), aOR 2.22, CI 1.13-4.85…”
mentioning
confidence: 99%